THE INFLUENCE OF ALUMNI KNOWLEDGE AND INTEREST ON JOB OPPORTUNITIES IN THE ACCOUNTING STUDY PROGRAM OF SHARIA FINANCIAL INSTITUTIONS AT IAIN PAREPARE - Adianti, Viviany (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2025)
This study aims to determine the influence of knowledge and interest on job opportunities in Islamic financial institutions among alumni of the Accounting Study Program at IAIN Parepare. This is a quantitative study with an associative approach. The sampling technique used was purposive sampling. Data collection was conducted by distributing questionnaires to alumni of the Islamic financial institutions accounting study program at IAIN Parepare. The sample size was 66 respondents. The data analysis technique used was multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) Version 26. The results of this study indicate that knowledge has a significant partial effect on job opportunities in Islamic financial institutions, with a calculated t value > t table (3.147 > 1.998), and interest has a significant effect on job opportunities in Islamic financial institutions, with a calculated t value > t table (6.434 > 1.998). Simultaneously, knowledge and interest significantly influence job opportunities in Islamic financial institutions, with a calculated F value > F table (46.460 > 3.15). This means that the higher a person's level of knowledge and interest, the greater their chances of getting a job in an Islamic financial institution.